2016
DOI: 10.1101/cshperspect.a027094
|View full text |Cite|
|
Sign up to set email alerts
|

Reengineering the Tumor Microenvironment to Alleviate Hypoxia and Overcome Cancer Heterogeneity

Abstract: Solid tumors consist of cancer cells and stromal cells, including resident and transiting immune cells—all ensconced in an extracellular matrix (ECM)—nourished by blood vessels and drained by lymphatic vessels. The microenvironment constituents are abnormal and heterogeneous in morphology, phenotype, and physiology. Such irregularities include an inefficient tumor vascular network comprised of leaky and compressed vessels, which impair blood flow and oxygen delivery. Low oxygenation in certain tumor regions—or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
121
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 235 publications
(309 reference statements)
1
121
0
Order By: Relevance
“…enhance understanding of nanoparticle performance in animal models (24)(25)(26)(27), strategies to normalize tumor vasculature (28), systematic investigations into ideal nanoparticle characteristics (24,29), and a focus on smaller (20-30-nm-sized) nanocarriers (24,30,31). Despite the promise of these approaches, the diversity of human cancers necessitates equivalently diverse delivery approaches (23,32) and opportunity for improvement remains, particularly in the area of enhancing uniformity of tumor distribution.…”
mentioning
confidence: 99%
“…enhance understanding of nanoparticle performance in animal models (24)(25)(26)(27), strategies to normalize tumor vasculature (28), systematic investigations into ideal nanoparticle characteristics (24,29), and a focus on smaller (20-30-nm-sized) nanocarriers (24,30,31). Despite the promise of these approaches, the diversity of human cancers necessitates equivalently diverse delivery approaches (23,32) and opportunity for improvement remains, particularly in the area of enhancing uniformity of tumor distribution.…”
mentioning
confidence: 99%
“…Tumors are complex tissues consisting of cancer cells and their microenvironment [1,2], which includes structural and cellular components. Structural components of the tumor microenvironment comprise tumor blood and lymphatic vessels, and the extracellular matrix (ECM) (see Glossary); while the stromal cell constituents [3] include angiogenic vascular cells (endothelial cells and pericytes), infiltrating immune cells, and cancer-associated fibroblasts (CAFs).…”
Section: The Tumor Microenvironment and Drug Deliverymentioning
confidence: 99%
“…Stress alleviation strategies are based on the concept that desmoplasia hinders proper drug delivery by compressing intratumoral blood vessels, and thus agents that relief the stress accumulated by ECM components will facilitate vessel decompression, improve perfusion, and enhance delivery of chemotherapy [2,14,15]. In fact, repurposing of common anti-fibrotic drugs to reduce collagen and/or hyaluronan levels when combined with cytotoxic drugs has shown to cause stress alleviation and improve overall survival of mice-bearing tumors [16][17][18].…”
Section: Strategies To Improve Drug Deliverymentioning
confidence: 99%
“…Most recently, the dramatic success of immunotherapy in metastatic melanoma (1), non-small cell lung cancer (NSCLC) (2,3), as well as multiple other cancer types has shown that modulation of the immune microenvironment can be an effective therapeutic strategy. It is now clear that the tumor microenvironment is a hypoxic milieu that promotes immunosuppression via T-cell exhaustion, anergy, accumulation of immunosuppressive cell types, among numerous other mechanisms (4). …”
mentioning
confidence: 99%
“…For example, tumors are quite hypoxic due to leaky vessel formation (17), vessel compression (18), and mechanical stress resulting from desmoplastic tumor stroma (19). This tumor hypoxia promotes an immunosuppressive environment (4), which may impede response to immune checkpoint blockade. Thus, strategies to normalize the vasculature in tumors during or after chemoradiotherapy may improve the likelihood of response to immune checkpoint inhibition.…”
mentioning
confidence: 99%